PENANAMAN NILAI-NILAI KEISLAMAN BAGI ANAK USIA DINI - Eti Nurhayati (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2016)
ABSTRACTAlong with the progress achieved in the current era of globalization, there is a crisis of moral and religious. Various delinquency increasingly become a phenomenon among teens and adults, in addition to the commitment and consistent of religious has not been seen in some teenagers and adults. It is pointed out, due to religious education and Islamic values are less effective when they were inculcated in early childhood. Therefore, inculcate Islamic values to children as early as possible is very important because it will become the foundation for their life as an adult. This study aims to: (1) formulating the Islamic values that are important inculcated to early childhood, (2) explore the potential of children that can be developed to inculcate Islamic values to them, (3) identify methods and strategies effective to inculcate Islamic values to early childhood. This study uses descriptive qualitative, data collection techniques using intensive observation of the learning process and in-depth interviews and then analyzed qualitatively in narrative form.Results of this study conclude: (1) The Islamic values are important to early childhood inculcated includes four major components, namely: the values of faith, worship, akhlaq karimah, and reading the Qur'an. (2) Some of the potential early childhood include the potential physical and psychological, such as: physical, brain, motivation, attention, memory, and cognitive foundations on which to accept Islamic values inculcated to them. (3) The method effectively used, such as: the provision of religious knowledge in an integrated way or separately with each theme, habituation, warning, giving the example, create an religious environment, cooperation with parents in the religious education of children in the family, such as: habituation prayer, fasting, manners of interacting, and particularly in learning to read the Qur'an. An effective strategy is mainly done by the principle of